Does regular quality control improve the quality of surgery in Slovenian breast cancer screening program? - Perhavec, Andraž (Radiology and oncology (Ljubljana), 2020)
The aim of our study was to evaluate the quality of surgery of Slovenian breast cancer screening program (DORA) using the requested EU standards. Furthermore, we investigated whether regular quality control over the 3-year period improved the quality of surgical management. Patients and methods. Patients who required surgical management within DORA between January 1st, 2016 and December 31st, 2018 were included in the retrospective study. Quality indicators (QIs) were adjusted mainly according to European Society of Breast Cancer Specialists (EUSOMA) and European Breast Cancer Network (EBCN) recommendations. Five QIs for therapeutic and two for diagnostic surgeries were selected. Additionally, variability in achieving the requested QIs among surgeons was analysed. Results. Between 2016 and 2018, 14 surgeons performed 1421 breast procedures in 1398 women. There were 1197 therapeutical (for proven breast cancer) and 224 diagnostic surgical interventions respectively. Overall, the minimal standard was met in two QIs for therapeutic and none for diagnostic procedures. A statistically significant improvement in three QIs for therapeutic and in one QI for diagnostic procedures was observed however, indicating that regular quality control improves the quality of surgery. A high variability in achieving the requested QIs was observed among surgeons, which remained high throughout the study period. Conclusions. Adherence to all selected surgical QIs in patients from screening program is difficult to achieve, especially to those specifically defined for screen-detected lesions. Regular quality control may improve results over time. Reducing the number of surgeons dedicated to breast pathology may reduce variability of management inside the institution.
Keywords: dojke; kirurško zdravljenje; mamografija; presejalni programi